Oil/water interfaces of guar gum-based biopolymer hydrogels and application to their separation - Dai, Lei; Wang, Baobin; An, Xingye; Zhang, Liqiang; Khan, Avik; Ni, Yonghao (Carbohydrate polymers, 2017)
•This paper describes an innovative biodegradable and biocompatible hydrogel material for oily waste water separation.•The as-prepared guar gum hydrogel-coated material showed high oil/water separation efficiency.•The resultant material has ultralow oil adhesion and it is easy to be recycled.•This work provides a fluoride-free and sustainable approach to realize the separation of highly-viscous oil from water. Oily wastewater treatment has become a significant research subject due to potential environmental related applications, e.g., oil spill remedy process. In this paper, a natural polymer based hydrogel, prepared from guar gum (GG) and metaborate, was coated onto a stainless steel mesh, and the as-prepared hydrogel-coated material was applied for oil/water separation. The strong hydrophilic GG hydrogel imparted excellent underwater oleophobicity and ultra-low oil adhesion. The results proved that the as-prepared GG hydrogel-coated material possessed excellent self-cleaning property and high oil/water separation efficiency